Analysis of Bed Load in Cibanjaran River, Tasikmalaya Regency, West Java - Ahmad Fakhrur Rozi; Rakhmat Yusuf (Universitas Negeri Semarang, 2025)
Cibanjaran River is one of the rivers located in the Galunggung Mountain area, with abundant sand sources, so there is sand mining. Cibanjaran River experiences the impact of mining, one of which is sedimentation. This study aims to determine the mass and mass distribution of bed load of Cibanjaran River from upstream to downstream. It also analyzes the gradation of basic sediments, sediment transport with the Schoklitsch method (1935), and simulations using HEC-RAS 6.5 software. Based on the results of the study, the upstream bottom sediment is poorly graded gravel with sand, the middle is well-graded sand with gravel, and the downstream is poorly graded gravel with sand. It has a specific gravity of 2.75 - 2.8. The mass transport of bottom sediment using the Schoklitsch calculation method is upstream 22,383.53 tons/day, middle 7,844.56 tons/day, and downstream 10,561.30 tons/day. While the results of the HEC-RAS 6.5 simulation produced a mass of sediment transport in the upstream Sta. 10833, which is 26,217.41 tons/day, in the middle of Sta. 6399 is 4,502.31 tons/day, and downstream Sta. 13 is 10,517.47 tons/day. The results of calculations and simulations can be a reference in strategic planning to mitigate the impact of sedimentation, so it is necessary to control mining activities and optimize sediment control infrastructure to maintain the sustainability of the river ecosystem and minimize negative impacts on surrounding communities.